Impact of enhanced metabolic stability on pharmacokinetics and pharmacodynamics of GalNAc–siRNA conjugates. Issue 19 (15th September 2017) - Nair, Jayaprakash K.; Attarwala, Husain; Sehgal, Alfica; Wang, Qianfan; Aluri, Krishna; Zhang, Xuemei; Gao, Minggeng; Liu, Ju; Indrakanti, Ramesh; Schofield, Sally; Kretschmer, Philip; Brown, Christopher R.; et al.
Abstract: Covalent attachment of a synthetic triantennary N -acetylagalactosamine (GalNAc) ligand to chemically modified siRNA has enabled asialoglycoprotein (ASGPR)-mediated targeted delivery of therapeutically active siRNAs to hepatocytes in vivo . This approach has become transformative for the delivery of RNAi therapeutics as well as other classes of investigational oligonucleotide therapeutics to the liver. For efficient functional delivery of intact drug into the desired subcellular compartment, however, it is critical that the nucleic acids are stabilized against nucleolytic degradation. Here, we compared two siRNAs of the same sequence but with different modification pattern resulting in different degrees of protection against nuclease activity. In vitro stability studies in different biological matrices show that 5′-exonuclease is the most prevalent nuclease activity in endo-lysosomal compartments and that additional stabilization in the 5′-regions of both siRNA strands significantly enhances the overall metabolic stability of GalNAc–siRNA conjugates. In good agreement with in vitro findings, the enhanced stability translated into substantially improved liver exposure, gene silencing efficacy and duration of effect in mice. Follow-up studies with a second set of conjugates targeting a different transcript confirmed the previous results, provided additional insights into kinetics of RISC loading and demonstrated excellent translation to non-human primates.